Intracellular IL-4 and IFN-γ expression in iNKT cells from patients with chronic lymphocytic leukemia - Bojarska-Junak, Agnieszka (Oncol Lett, 2018)
Malignant B cells in chronic lymphocytic leukemia serve an essential role in the whole immune response, so their interactions with other immune cells are more complex than observed in solid tumors. The latest study results indicate that the immune dysregulation in chronic lymphocytic leukemia (CLL) also affects a small population of invariant natural killer T cells (iNKT). Using peripheral blood iNKT cells obtained from patients with CLL, the objective of the present study was to assess the intracellular expression of typical cytokines involved in the Th1 (IFN-γ) and Th2 (IL-4) response pathways following stimulation with the iNKT-specific ligand α-galactosylceramide. iNKT cells from patients with CLL exhibited upregulated IL-4 and IFN-γ expression in comparison to those from HVs. No significant association between the ability of iNKT cells to produce IL-4 or IFN-γ and the expression of CD1d on leukemic B lymphocytes or monocytes was identified. However, the function of iNKT cells was compromised in patients with CLL by a strong Th2 bias (high IL-4 and low IFN-γ expression). The ratio of iNKT(+)IFN-γ(+):iNKT(+)IL-4(+) was significantly decreased in the CLL group when compared with HVs, and this decreased further as the disease progressed. This change may result in the promotion of leukemic B lymphocyte survival. Therefore, in the pathogenesis of CLL, Th2 bias may delay the antitumor response that relies on stimulation of the Th1 immune response.